Floquet operator engineering for quantum state stroboscopic stabilization - Arrouas, Floriane; Ombredane, Nicolas; Gabardos, Lucas; Dionis, Etienne; Dupont, Nathan; Billy, Juliette; Peaudecerf, Bruno; Sugny, Dominique; Guéry-Odelin, David (Comptes Rendus. Physique)
Optimal control is a valuable tool for quantum simulation, allowing for the optimized preparation, manipulation, and measurement of quantum states. Through the optimization of a time-dependent control parameter, target states can be prepared to initialize or engineer specific quantum dynamics. In this work, we focus on the tailoring of a unitary evolution leading to the stroboscopic stabilization of quantum states of a Bose–Einstein condensate in an optical lattice. We show how, for states with space and time symmetries, such an evolution can be derived from the initial state-preparation controls; while for a general target state we make use of quantum optimal control to directly generate a stabilizing Floquet operator. Numerical optimizations highlight the existence of a quantum speed limit for this stabilization process, and our experimental results demonstrate the efficient stabilization of a broad range of quantum states in the lattice.